Kluver–Bucy syndrome in one case with systemic lupus erythematosus - Lin, Hsiu-Fen; Yeh, Yi-Chun; Chen, Chien-Fu; Chang, Wei-Chen; Chen, Cheng-Sheng; 林秀芬; 葉怡君; 陳建甫; 張瑋真; 陳正生 (The Kaohsiung journal of medical sciences, 2011)
Kluver–Bucy syndrome (KBS) is a collection of neuropsychiatric symptoms, including visual agnosia (prosopagnosia), hypermetamorphosis, placidity, hypersexuality, and hyperorality. Although neuropsychiatric manifestation is prevalent in cases with systemic lupus erythematosus (SLE), only one literature reported a case with SLE that had KBS previously. In this article, a 37-year-old woman with SLE who developed KBS and other neuropsychiatric symptoms is presented. Brain imaging proved the relevant structural lesion. The possible explanation of pathogenesis of KBS in SLE is discussed. Kluver-Bucy 症候群包括視覺不能、異常衝動性的反應、過於馴服、性慾增加、與口慾增加等表現。雖然紅斑性狼瘡或者常有神經精神症狀，但文獻中僅有一例Kluver-Bucy症候群的報告。本文報告一例37歲的紅斑性狼瘡女性患者，表現出典型的Kluver-Bucy症候群。腦影像支持其有相對應的雙側前顳葉的結構變化，可能的致病機轉將在本文進一步討論。